PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP PRODUKTIVITAS KARYAWAN DI PT. SURYA MANDIRI PRATAMA PEKANBARU - Angga Gusti Satria; Susi Hendriani; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study held in PT. Surya Mandiri Pratama Pekanbaru. The aim is to analyze the influence of work-related discipline and organizational commitment to employee’s productivity. Population are all employee’s, consist of 85 employees that selected by using cencus method. Variables are work-related discipline and organizational commitment as independents and productivity as depenedent. Data analyzed by using descriptive and multiple linear regression analysis assisted by SPSS 17 for windows. The study reveals that both work-related discipline and organizational commitment significantly influence employees’ productivity either partially or simultaneously. Work-related discipline has the stronger effect to employees’ productivity rather than organizational commitment. It is recommended to management in order to enhance discipline program and the organizational commitment, particularly, rules socialization, consistant reward and punishment implementation, individual value and organization harmonization.Keywords: Work-related Discipline, Organizational, Commitment, and Productivity